ATP Synthase K+- and H+-fluxes Drive ATP Synthesis and Enable Mitochondrial K+-"Uniporter" Function: II. Ion and ATP Synthase Flux Regulation. Issue 2 (27th January 2022) - Juhaszova, Magdalena; Kobrinsky, Evgeny; Zorov, Dmitry B; Nuss, H Bradley; Yaniv, Yael; Fishbein, Kenneth W; de Cabo, Rafael; Montoliu, Lluis; Gabelli, Sandra B; Aon, Miguel A; Cortassa, Sonia; Sollott, Steven J
Abstract: We demonstrated that ATP synthase serves the functions of a primary mitochondrial K + "uniporter, " i.e., the primary way for K + to enter mitochondria. This K + entry is proportional to ATP synthesis, regulating matrix volume and energy supply-vs-demand matching. We show that ATP synthase can be upregulated by endogenous survival-related proteins via IF1 . We identified a conserved BH3-like domain of IF1 which overlaps its "minimal inhibitory domain" that binds to the β-subunit of F1 . Bcl-xL and Mcl-1 possess a BH3-binding-groove that can engage IF1 and exert effects, requiring this interaction, comparable to diazoxide to augment ATP synthase's H + and K + flux and ATP synthesis. Bcl-xL and Mcl-1, but not Bcl-2, serve as endogenous regulatory ligands of ATP synthase via interaction with IF1 at this BH3-like domain, to increase its chemo-mechanical efficiency, enabling its function as the recruitable mitochondrial KATP -channel that can limit ischemia-reperfusion injury. Using Bayesian phylogenetic analysis to examine potential bacterial IF1 -progenitors, we found that IF1 is likely an ancient (∼2 Gya) Bcl-family member that evolved from primordial bacteria resident in eukaryotes, corresponding to their putative emergence as symbiotic mitochondria, and functioning to prevent their parasitic ATP consumption inside the host cell. Graphical Abstract: